Two phase microstructure cycling of porous silicon active materials. (May 2020) - Entwistle, Jake
Abstract: Silicon is well known to provide a step change in capacity for lithium-ion battery anodes. We present our thoughts on using porous silicon active materials and the two phase microstructure approach to control silicon volume expansion and capacity during lithiation. With this method silicon can be tailored to the specific cell application desirable by controlling the volume expansion and capacity. The initial results show a negative impact of using controlled capacity activation of porous silicon relative to the control sample which is galvanostatically cycled. We highlight our next steps in exploring this approach.